Setting the Deadline for Nuclear Weapon Removal from Host States under the Treaty on the Prohibition of Nuclear Weapons - Moritz Kütt; Zia Mian (Journal for Peace and Nuclear Disarmament, 2022)
The Treaty on the Prohibition of Nuclear Weapons requires that states which join the treaty while hosting nuclear weapons, “shall ensure the prompt removal of such weapons, as soon as possible but not later than a deadline to be determined by the first meeting of States Parties”. This article offers a basis for setting the weapon removal deadline under the new treaty. It describes briefly the experience of past removals of nuclear weapons from deployment in Cuba, East Germany, Taiwan, Hungary, South Korea, and Greece. It then outlines a plausible process of nuclear weapon removal from the current five nuclear weapon host countries, all holding nuclear weapons belonging to the United States, that reflects existing US nuclear weapon transport practices and capabilities. The analysis suggests the parties to the Treaty on the Prohibition of Nuclear Weapons could set a 90 day deadline for the safe and secure removal of nuclear weapons from host states.